Penerapan Pasal 6 Peraturan Walikota Gorontalo Nomor 37 Tahun 2019 Tentang Implementasi Pendidikan Antikorupsi Di Smpn 4 Gorontalo - Yusuf, Yurinda; Djaafar, Lucyane; Mozin, Nopiana (Universitas Pahlawan Tuanku Tambusai, 2024)
Corruption is a serious issue in Indonesia, with wide-ranging impacts across various sectors. According to data from Transparency International, Indonesia ranks 96th out of 180 of the most corrupt countries. To address this issue, since December 2018, the Corruption Eradication Commission (KPK), in collaboration with the Ministry of Education and Culture (Kemendikbud), has integrated anti-corruption education into the national curriculum. As a follow-up, the Government of Gorontalo City issued Mayor Regulation Number 37 of 2019 on the Implementation of Anti-Corruption Education, which mandates the implementation of such education at all educational levels. This study aims to (1) Analyze the implementation of Article 6 of Mayor Regulation Number 37 of 2019 at SMP Negeri 4 Gorontalo, and (2) Identify the factors hindering the implementation of the regulation. The research employs a descriptive qualitative method. The findings indicate that the implementation of Article 6 has not been effective. The obstacles identified include: (a) Ineffective communication, particularly in delivering information; (b) Limited resources, especially due to the varying character of the school community, leading to discipline issues; (c) Lack of initiative from policy implementers to seek additional information; and (d) Bureaucratic structures that do not align with Article 6 of the Mayor Regulation, resulting in suboptimal implementation of anti-corruption education policies at SMP Negeri 4 Gorontalo.